Recommendations on telestroke in Europe. (June 2019) - Hubert, Gordian J; Santo, Gustavo; Vanhooren, Geert; Zvan, Bojana; Tur Campos, Silvia; Alasheev, Andrey; Abilleira, Sònia; Corea, Francesco
Lack of stroke specialists determines that many European rural areas remain underserved. Use of telemedicine in stroke care has shown to be safe, increase use of evidence-based therapy and enable coverage of large areas of low population density. The aim of this article is to summarise the following recommendations of the Telestroke Committee of the European Stroke Organisation on the setup of telestroke networks in Europe: Hospitals participating in telestroke networks should be chosen according to criteria that include population density, transportation distance, geographic specifics and in-hospital infrastructure and professional resources. Three hospital categories are identified to be part of a hub-and-spoke network: (1) the Telemedicine Stroke Centre (an European Stroke Organisation stroke centre or equivalent with specific infrastructure and setup for network and telemedicine support), (2) the telemedicine-assisted stroke Unit (equivalent to an European Stroke Organisation stroke unit but without 24 h onsite stroke expertise) and (3) the telemedicine-assisted stroke ready hospital (only covering hyperacute treatment in the emergency department and transferring all patients for further treatment).